ANALISIS YURIDIS JUAL BELI BARANG MELALUI MARKETPLACE DITINJAU DARI HUKUM POSITIF - NIM. A1012181053, RIZQY DWI PUTRA (Jurnal Fatwa Hukum, 2025)
AbstractTechnological advancements have transformed buying and selling transaction patterns, where marketplace platforms have become the primary method replacing conventional transactions. However, this convenience also raises various legal issues, such as product discrepancies, seller fraud, and marketplace liability in problematic transactions. This study aims to analyze buying and selling transactions through marketplaces from the perspective of positive law, particularly regarding consumer protection and the rights and obligations of the parties involved. This research employs a normative juridical method with a literature study approach based on the Indonesian Civil Code (KUHPerdata), the Consumer Protection Law (UU Perlindungan Konsumen), and the Electronic Information and Transactions Law (UU ITE). The findings indicate that although regulations have been established for online transactions, their implementation still faces challenges, especially in terms of consumer protection effectiveness. Several cases show that the complaint and dispute resolution mechanisms provided by marketplaces remain limited, often failing to offer fair solutions for consumers. Therefore, improvements in regulations and marketplace policies are necessary to ensure that return and dispute resolution mechanisms operate more transparently, quickly, and efficiently in protecting consumer rights.  Keywords: Buying; Selling; Transactions; Electronic; Marketplace.    AbstrakPerkembangan teknologi telah mengubah pola transaksi jual beli, di mana platform marketplace menjadi metode utama yang menggantikan transaksi konvensional. Namun, kemudahan ini juga menimbulkan berbagai permasalahan hukum, seperti ketidaksesuaian barang, penipuan oleh penjual, serta pertanggungjawaban marketplace dalam transaksi yang bermasalah. Penelitian ini bertujuan untuk menganalisis transaksi jual beli barang melalui marketplace dalam perspektif hukum positif, khususnya terkait perlindungan konsumen serta hak dan kewajiban para pihak. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan studi kepustakaan terhadap KUHPerdata, UU Perlindungan Konsumen, dan UU ITE. Hasil penelitian menunjukkan bahwa meskipun regulasi telah mengatur transaksi online, implementasinya masih memiliki kendala, terutama dalam efektivitas perlindungan konsumen. Beberapa kasus menunjukkan bahwa mekanisme pengaduan dan penyelesaian sengketa yang disediakan marketplace masih memiliki keterbatasan, sehingga tidak selalu memberikan solusi yang adil bagi konsumen. Untuk itu diperlukan peningkatan regulasi dan kebijakan marketplace guna memastikan mekanisme pengembalian barang dan penyelesaian sengketa dapat berjalan lebih transparan, cepat, dan efisien dalam melindungi hak konsumen.  Kata kunci: Jual, Beli, Transaksi, Elektronik, Marketplace.